Black Cohosh and Liver Toxicity: Is There a Relationship?. (30th June 2014) - Muqeet Adnan, Mohammed; Khan, Muhammad; Hashmi, Syed; Hamza, Muhammad; AbdulMujeeb, Sufyan; Amer, Syed
Abstract : Herbal supplements are commonly used by patients for various problems. It is a well-known fact that most patients do not tell their physicians about the use of herbal supplements unless they are specifically asked. As a result, sometimes important information regarding drug side effects is missed in history taking. During our literature search, we found several retrospective studies and other meta-analyses that claim a lacking or weak link between black cohosh use and hepatotoxicity. We present a case of a 44-year-old female who developed subacute liver injury demonstrated on a CT scan and liver biopsy within a month of using the drug to resolve her hot flashes and discuss a possible temporal and causal association between black cohosh use and liver disease. Since the patient was not taking any other drugs, we concluded that the acute liver injury was caused by the use of black cohosh. We agree with the United States Pharmacopeia recommendations that a cautionary warning about hepatotoxicity should be labeled on the drug package.